Cationic modified brocade cotton blended fabric and dyeing method thereof
Through the coordinated complex modification of natural cationic polymers and metal salts, the problem of long process flow and high pollution in the dyeing process of traditional brocade cotton blended fabrics is solved, and the efficient one-bath acid dyeing is achieved, which improves production efficiency and dyeing effect, meets green production requirements.
Patent Information
- Application Number
- CN202411278115.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-27
AI Technical Summary
The dyeing process of traditional brocade cotton blended fabrics has problems such as long process flow, low processing quality, large energy consumption, high pollution emissions and poor economic benefits, and it is difficult to meet the dyeing needs of nylon and cotton fibers at the same time.
The nylon fiber is treated with collaborative complex modification of natural cationic polymer and metal salt. The nylon fiber is used to dye the one-bath one-step dyeing method. Cationic modification improves its adsorption ability to acid dyes and achieves efficient dyeing.
It significantly reduces pollution problems during the dyeing process, improves dyeing efficiency and production efficiency, reduces the use of chemical agents, meets the requirements of green production, and obtains products with bright colors, soft feel and excellent performance.
Smart Images

Figure CN119194877A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of textiles, and particularly relates to a cationic modified nylon-cotton blended fabric and a dyeing method thereof. Background Art
[0002] Nylon-cotton blended fabrics are favored by consumers due to their good moisture absorption and breathability, excellent resilience, high strength and wear resistance. However, due to the large differences in the properties of cotton and nylon fibers, traditional dyeing methods often cannot meet the dyeing needs of nylon and cotton fibers at the same time, resulting in some problems in dyeing. The main dyeing processes currently include one-bath process and two-bath process.
[0003] The one-bath process usually uses acid or neutral / direct dyes for dyeing. However, due to the poor wet fastness of direct dyes, the color fastness performance cannot meet product requirements. Some methods use acid dyes for one-bath one-step dyeing, but the cotton fiber needs to be cationic modified before dyeing. Cationic modification can improve the dyeability of the fabric, but the modification itself consumes a lot of auxiliaries and time, and the recovery of the modified liquid is also problematic. Other methods use reactive dyes for one-bath dyeing, but these reactive dyes need to be microencapsulated, which increases the dyeing process flow and cost, and the choice of dyes is limited.
[0004] At present, factories generally use acid or neutral / reactive dyes for two-bath dyeing. However, this process has problems such as high production cost, long processing cycle, high energy consumption, and large amount of wastewater. In recent years, with the continuous improvement of low-salt and low-alkali reactive dye processing technology, one-bath two-step dyeing using acid or neutral / reactive dyes has become a hot topic of research. Compared with the traditional two-bath process, this dyeing process is shorter, and the discharge of dyeing wastewater and energy consumption are greatly reduced. At the same time, the color fastness of the product is also higher. For example, there is a method that uses reactive dyes for acid dyeing and alkaline fixation in one bath and two steps, and both dyeability and homochromaticity have achieved good results. Some people also use neutral dyes / thermosetting reactive dyes for bath dyeing, and dyeing is carried out under neutral medium and 100-110℃. However, this method requires the use of reactive dyes that are fixed under neutral conditions with higher costs, so it is rarely used by factories.
[0005] In summary, there are still some challenges in the dyeing of nylon-cotton blended fabrics. It is urgent to explore new dye selection or modification methods to achieve better dyeing effects and higher production efficiency. Summary of the invention
[0006] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a cationic modified nylon-cotton blended fabric and a dyeing method thereof, which overcomes the defects of the conventional nylon-cotton blended fabric dyeing process in the prior art, such as long process flow, low processing quality, high energy consumption, high pollution emission, serious dye staining and poor economic benefits. The technical solution of the present invention can greatly reduce the pollution problem in the dyeing process through cationic modification treatment and one-bath one-step dyeing, while significantly improving the dyeing efficiency, thereby improving the production efficiency of industrial production.
[0007] The invention provides a modified finishing liquid, which comprises a mixed solution of a first solution, a second solution and a third solution; wherein the first solution comprises a natural cationic polymer solution; the second solution comprises a metal salt solution; the third solution comprises a mixed solution of citric acid, sodium hypophosphite and triethanolamine; wherein the finishing liquid also comprises a penetrant.
[0008] Preferably, the volume ratio of the first solution to the second solution is 1:1-1:3; the volume ratio of the mixture of the first solution and the second solution to the third solution is 1:1-1:5; and the penetrant is 0.05-0.5 g / L.
[0009] Preferably, the first solution: a natural cationic polymer is dispersed in deionized water, diluted acid is added to fully dissolve it, and then the pH is adjusted to 5-6 with alkali solution; wherein the natural cationic polymer is chitosan, and the content is 0.1-1g / L; the diluted acid is one or more of glacial acetic acid, lactic acid, citric acid, and tartaric acid; and the alkali solution is sodium hydroxide or potassium hydroxide.
[0010] Preferably, the metal salt is at least one of a calcium salt, a copper salt and a zinc salt; the solvent of the second solution is water; the calcium salt in the second solution is 0.005-0.05 g / L, the copper salt is 0.005-0.05 g / L, and the zinc salt is 0.005-0.05 g / L; the calcium salt is calcium chloride; the copper salt is copper sulfate; and the zinc salt is zinc sulfate.
[0011] Preferably, the content of citric acid in the third solution is 0.1-1 g / L, the content of sodium hypophosphite is 0.1-1 g / L, and the content of triethanolamine is 0.1-1 g / L.
[0012] The modified finishing liquid is prepared by mixing the first solution and the second solution, then mixing with the third solution, and then adding the penetrant and stirring evenly.
[0013] The invention provides a modified finished fabric, wherein the fabric is treated with the modified finishing agent; wherein the fabric is a nylon-cotton blended fabric; the nylon content of the nylon-cotton blended fabric is 20-50%, and the cotton content is 50-80%.
[0014] The invention provides a method for preparing the modified finished fabric, comprising: adding the fabric into the modified finishing liquid, performing modification treatment, and then performing heat treatment under the condition of liquid carrying rate, and drying to obtain the modified finished fabric.
[0015] Preferably, the fabric is a nylon-cotton blended fabric; the nylon content of the nylon-cotton blended fabric is 20-50%, and the cotton content is 50-80%.
[0016] Preferably, the bath ratio of the fabric to the modified finishing liquid is 1:4 to 1:10;
[0017] Preferably, the modification treatment temperature is 60-100°C, the time is 10-60 minutes, and the liquid carrying rate after treatment is 70-120%;
[0018] Preferably, the heat treatment temperature is 60-80° C., and the time is 5 min-30 min; and the heat treatment is performed in a resistance furnace.
[0019] Preferably, the drying temperature is 60-80° C., the drying time is 5-10 min; and the drying is carried out in an oven.
[0020] The invention provides a dyed fabric, which is characterized in that the modified finished fabric is dyed, wherein the dye is an acid dye.
[0021] The invention provides a method for preparing a dyed fabric, comprising: adding a modified finished fabric into a dye liquor for one-bath dyeing, then washing, fixing the color, and drying to obtain the dyed fabric; wherein the dye is an acid dye.
[0022] Preferably, the specific dyeing process is to start dyeing at room temperature, then increase the temperature to 70-100°C at 0.5-2.5°C / min and dye for 20-60min; the washing process conditions are: first wash with 70°C hot water, then wash with 45°C warm water, and finally wash with cold water; the fixing conditions are to use 0.5-2g / L dilute acid for fixing at 80°C for 20min, and the specific dilute acid is any one of glacial acetic acid or tannic acid.
[0023] Preferably, the acid dye is an acid dye containing anionic groups (such as sulfonic acid groups, carboxyl groups and other anionic groups) in the molecular structure; the amount of the acid dye is 0.5-10% of the weight of the fabric, and the dyeing bath ratio is 1:5-1:20.
[0024] The acid dyes are acid red A, acid red G, acid orange II, acid yellow 2G and the like.
[0025] Preferably, the dye liquor further comprises a leveling agent and a pH adjusting agent; wherein the leveling agent is a compound of alkylamine polyoxyethylene ether and sodium alkyl aryl sulfonate, wherein the content of alkylamine polyoxyethylene ether is 0.5-1.5 g / L, and the content of sodium alkyl aryl sulfonate is 0.5-1.5 g / L; and the pH adjusting agent is glacial acetic acid-ammonium acetate, and the pH of the dye bath is adjusted to 3-7.
[0026] In the present invention, natural cationic polymers and metal salts are used to carry out synergistic complex modification on nylon-cotton blended fabrics, and then the surface cationic modification of nylon-cotton blended fibers is achieved through an impregnation + heat treatment process, thereby improving the dyeability of nylon-cotton blended fabrics. The macromolecules in nylon fibers are arranged regularly and neatly, and the high crystallinity weakens its adsorption capacity for anionic dyes during the dyeing process, thereby reducing its dyeability. Cotton fibers are negatively charged in solution, which reduces their adsorption between dye anions, making them less dyeable for dyes with anionic groups. The use of natural cationic polymer chitosan, which is efficient, environmentally friendly, and biocompatible, as a cationic modifier to modify nylon-cotton blended fibers can make the modified fibers overall positively charged, which is more conducive to dyeing acid dyes containing anionic groups such as sulfonic acid groups / carboxyl groups. In addition, the main structure of nylon fiber contains a large number of reactive amide groups, and the structure of cotton fiber also contains hydroxyl groups with certain reactivity. Some metal ions (calcium ions, copper ions, zinc ions) can react with amide groups and hydroxyl groups to form complexes. The complexation can successively destroy the regularity and crystallization area of the molecular chain on the fiber surface, reduce the crystallinity, and improve the dyeability of blended fabrics. The surface of the modified nylon-cotton blended fabrics is positively charged, and the negative charge structure of the acid dye attracts it, thereby improving the directness of the blended fabrics and the acid dyes, and realizing the one-bath one-step dyeing of the modified blended fabrics with acid dyes.
[0027] The technical solution provided by the present invention can greatly reduce the pollution problem in the dyeing and finishing process, and can also significantly improve the dyeing efficiency compared with the existing technology, improve the production efficiency of industrial production of this type of process, and the dyeing effect is basically equivalent to traditional dyeing, saving economic costs for printing and dyeing enterprises.
[0028] Beneficial Effects
[0029] Compared with the traditional nylon-cotton blended fabric dyeing method, the cationic modified nylon-cotton blended fabric and the dyeing method thereof of the present invention can shorten the dyeing process, improve production efficiency, reduce energy consumption and environmental pollution. The method of the present invention can achieve efficient dyeing of nylon-cotton blended fabrics, with good dyeing homochromaticity, and can obtain products with bright colors, soft hand feeling and excellent performance. The method of the present invention can reduce the use of chemical agents, reduce pollution to the environment, and meet the requirements of green production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the process of the present invention.
[0031] Figure 2 The present invention is a one-bath dyeing process flow chart of the modified nylon-cotton blended fabric. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0033] Related tests:
[0034] K / S value, L*, a*, b* value: Fold the treated sample into 4 layers (opaque), and use a colorimeter to measure the K / S value, L*, a*, b* value of the fabric. Measure 4 different positions of the sample and take the average value. When testing single fibers, separate the cotton / nylon interwoven fabric into cotton fabric and nylon fabric, fold the separated single-component fabric until it is opaque, measure 4 different positions, and take the average value.
[0035] DE value (isochromaticity): Take a few points on the dyed sample and use a computer colorimeter to measure the L*, a*, and b* values at different points on the sample surface at the maximum absorption wavelength. Calculate the standard deviation. The smaller the DE value, the smaller the color difference and the better the homochromy.
[0036] Washing fastness: The color fastness to washing with soap is rated according to GB / T 3921-2008 "Textiles - Tests for Color Fastness - Color Fastness to Washing with Soap", and GB250-1995 "Grey Scale for Assessing Change in Color" and GB251-1995 "Grey Scale for Assessing Staining".
[0037] The color fastness to rubbing is measured and rated in accordance with GB / T 3920-2008 “Textiles - Tests for Color Fastness - Color Fastness to Rubbing”.
[0038] Material:
[0039] Chitosan (purity MW = 30000) was purchased from Shanghai Titan Technology Co., Ltd., nylon-cotton interwoven fabric (cotton 70 / nylon 30, 31S*100D, nylon is nylon 6, weight: 130 g / m 2 , provided by Yixing Leqi Textile Group Co., Ltd.).
[0040] Example 1
[0041] (1) Preparation of nylon-cotton blended fabrics
[0042] Prepare 30g of nylon-cotton blended fabric, in which the nylon content is 30% and the cotton content is 70%;
[0043] (2) Configuration of modified finishing liquid
[0044] Solution A: Disperse 0.3 g / L natural cationic polymer (chitosan) powder evenly in 50 mL of deionized water, add citric acid to fully dissolve it, and then adjust the pH to 5 with sodium hydroxide.
[0045] Solution B: Dissolve 0.005 g / L calcium chloride, 0.005 g / L copper sulfate, and 0.015 g / L zinc sulfate in 50 mL of deionized water. Add solution B to solution A while stirring to obtain solution C.
[0046] A certain amount of 0.5 g / L citric acid, 0.5 g / L sodium hypophosphite and 1 g / L triethanolamine were fully dissolved in 200 mL of deionized water and mixed evenly to obtain solution D.
[0047] After mixing solution C and solution D, 0.1 g / L of penetrant JFC was added and stirred evenly to finally obtain modifier finishing solution E.
[0048] (3) Cationic modification of nylon-cotton blended fabrics
[0049] The nylon-cotton blended fabric was added to the modified finishing liquid E, treated at 80°C for 30 minutes, then placed in a resistance furnace at a certain 100% liquid carrying rate, heat treated at 80°C for 10 minutes, and finally placed in an oven at 60°C for 5 minutes to obtain the modified nylon-cotton blended fabric.
[0050] (4) One-bath dyeing
[0051] The modified nylon-cotton blended fabric is added to 2% (owf) acid red G dye solution (600mL) for one-bath dyeing, then washed, fixed, and dried to obtain the dyed nylon-cotton blended fabric. The specific dyeing process is to adjust the pH of the dye bath to 4.5 with glacial acetic acid-ammonium acetate, the content of the leveling agent alkylamine polyoxyethylene ether is 0.5g / L, and the content of sodium alkyl aryl sulfonate is 0.5g / L. Dyeing begins at room temperature, and then the temperature is raised to 100°C at 2.5°C / min for dyeing for 20 minutes. The washing process conditions are: first wash with 70°C hot water, then wash with 45°C warm water, and finally wash with cold water; the fixing condition is to fix with 2g / L glacial acetic acid at 80°C for 20 minutes. The dye structure used in this embodiment is as follows:
[0052]
[0053] Example 2
[0054] The same parts as those in Example 1 are not described in detail. The difference is that in the modified finishing solution in step 2, the content of natural cationic polymer (chitosan) in solution A is 0.4 g / L, the content of calcium chloride in solution B is 0.01 g / L, the content of copper sulfate is 0.01 g / L, and the content of zinc sulfate is 0.025 g / L.
[0055] Example 3
[0056] The same parts as those of Example 1 are not described in detail. The difference is that the content of natural cationic polymer (chitosan) in solution A during the preparation of the modified finishing solution in step 2 is 0.4 g / L, the content of calcium chloride in solution B is 0.01 g / L, the content of copper sulfate is 0.01 g / L, and the content of zinc sulfate is 0.025 g / L. The concentration of acid red G dye in the one-bath dyeing process in step 4 is 3% (owf).
[0057] Example 4
[0058] The same parts of this embodiment as those of embodiment 1 are not described in detail. The difference is that the configuration and modification process of the cationic modification liquid in this embodiment are as follows:
[0059] Prepare 30g of nylon-cotton blended fabric, in which the nylon content is 30% and the cotton content is 70%, place the nylon-cotton blended fabric in 300mL of deionized water, add 6g of 3-chloro-2-hydroxypropyltrimethylammonium chloride and mix and react for 10min, then add 1.5g of sodium hydroxide and continue to react for 50min, then take out the nylon-cotton blended fabric and wash it with water, then treat it with 1g / L glacial acetic acid for 10min, then rinse with a large amount of clean water and dry it in an oven at 80°C to obtain a modified nylon-cotton blended fabric.
[0060] Example 5
[0061] The same parts as those of Example 1 are not described again. The difference is that this example does not undergo step 2 or step 3 cationic modification treatment.
[0062] The dyed nylon-cotton blended fabrics in the examples were subjected to the same color test, soap washing color fastness test and rubbing color fastness test. The test results are shown in Table 1 and Table 2.
[0063] Table 1 Dyeing homochromaticity difference test results
[0064]
[0065] Table 2 Color fastness test results
[0066]
[0067] It can be seen that in Examples 1, 2, and 3, the nylon-cotton blended fabric after cation modification of the present invention and the nylon-cotton blended fabric dyed by the acid dye nylon one-bath one-step method have good dyeing homochromaticity and high rubbing color fastness, wherein, by simultaneously increasing the concentration of the cationic modifier and the concentration of the dye in the dye solution, the blended fabric is dyed deeper and has good dyeing homochromaticity and color fastness. The present invention has a deeper dyeing, better dyeing homochromaticity, and better color fastness than the traditional cationic modification process (Example 4), and has certain technical advantages.
Claims
1. A modified finishing liquid, characterized in that: The finishing solution includes a mixed solution of a first solution, a second solution, and a third solution; The first solution comprises a natural cationic polymer solution; the second solution comprises a metal salt solution; and the third solution comprises a mixed solution of citric acid, sodium hypophosphite and triethanolamine; The finishing liquid further comprises a penetrant.
2. The modified finishing liquid according to claim 1, characterized in that: The volume ratio of the first solution to the second solution is 1:1 to 1:3; the volume ratio of the mixture of the first solution and the second solution to the third solution is 1:1 to 1:5; the penetrant is 0.05 to 0.5 g / L; The first solution: the natural cationic polymer is dispersed in deionized water, acid is added to fully dissolve it, and then the pH is adjusted to 5-6 with alkaline solution; The natural cationic polymer is chitosan with a content of 0.1-1 g / L; the acid is one or more of acetic acid, lactic acid, citric acid and tartaric acid; and the alkali solution is sodium hydroxide or potassium hydroxide.
3. The modified finishing liquid according to claim 1, characterized in that: The metal salt is at least one of calcium salt, copper salt and zinc salt; the solvent of the second solution is water; the calcium salt in the second solution is 0.005-0.05 g / L, the copper salt is 0.005-0.05 g / L, and the zinc salt is 0.005-0.05 g / L; the calcium salt is calcium chloride; the copper salt is copper sulfate; and the zinc salt is zinc sulfate.
4. The modified finishing liquid according to claim 1, characterized in that: The third solution contains 0.1-1 g / L citric acid, 0.1-1 g / L sodium hypophosphite and 0.1-1 g / L triethanolamine.
5. A modified finished fabric, characterized in that: The fabric is treated with the modified finishing agent according to claim 1.
6. A method for preparing the modified finished fabric according to claim 5, comprising: The fabric is added into the modified finishing liquid of claim 1 to perform a modification treatment, and then heat-treated under liquid carrying rate conditions and dried to obtain a modified finishing fabric.
7. The preparation method according to claim 6, characterized in that: The fabric is a nylon-cotton blended fabric; the nylon content of the nylon-cotton blended fabric is 20-50%, and the cotton content is 50-80%; The bath ratio of the fabric to the modified finishing liquid is 1:4 to 1:10; The modification treatment temperature is 60-100°C, the time is 10-60 minutes, and the liquid carrying rate after treatment is 70-120%; The heat treatment temperature is 60-80°C and the time is 5-30 minutes; The drying temperature is 60-80° C. and the drying time is 5-10 minutes.
8. A dyed fabric, characterized in that: The modified and finished fabric according to claim 5 is dyed; wherein the dye is an acid dye.
9. A method for preparing a dyed fabric, comprising: Adding the modified finished fabric according to claim 5 into a dye liquor for one-bath dyeing, followed by washing, color fixing, and drying to obtain a dyed fabric; The dye is an acid dye.
10. The preparation method according to claim 9, characterized in that: The acid dye is an acid dye containing an anionic group in the molecular structure; the amount of the acid dye is 0.5-10% of the weight of the fabric, and the dyeing bath ratio is 1:5-1:20; The dye liquor also includes a leveling agent and a pH regulator; wherein the leveling agent is alkylamine polyoxyethylene ether and alkylaryl sulfonic acid A compound of sodium, wherein the content of alkylamine polyoxyethylene ether is 0.5-1.5 g / L, and the content of sodium alkylaryl sulfonate is 0.5-1.5 g / L; The pH regulator is glacial acetic acid-ammonium acetate, and the pH of the dye bath is adjusted to 3-7.
